2006
DOI: 10.1007/s00439-006-0201-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization and fine mapping of susceptibility loci for sarcoidosis in African Americans on chromosome 5

Abstract: Sarcoidosis, a systemic granulomatous disease, likely results from both environmental agents and genetic susceptibility. Sarcoidosis is more prevalent in women and, in the United States, African Americans are both more commonly and more severely affected than Caucasians. We report a follow up of the first genome scan for sarcoidosis susceptibility genes in African Americans. Both the genome scan and the present study comprise 229 African American nuclear families ascertained through two or more sibs with sarco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 32 publications
2
20
0
2
Order By: Relevance
“…In addition, there was only modest agreement for linkage between the scans performed in the German and African American populations. In a follow-up study on the same patient population using additional microsatellite markers to refine regions with significant linkage, sarcoidosis susceptibility alleles were identified on chromosome 5p15.2 and protective alleles on chromosome 5q11.2 46. A further linkage analysis of the SAGA sample stratified by genetically determined ancestry (in order to reduce ethnic confounding) confirmed the peaks on chromosome 5 and revealed additional-associated loci 47…”
Section: Scanning the Genomementioning
confidence: 93%
“…In addition, there was only modest agreement for linkage between the scans performed in the German and African American populations. In a follow-up study on the same patient population using additional microsatellite markers to refine regions with significant linkage, sarcoidosis susceptibility alleles were identified on chromosome 5p15.2 and protective alleles on chromosome 5q11.2 46. A further linkage analysis of the SAGA sample stratified by genetically determined ancestry (in order to reduce ethnic confounding) confirmed the peaks on chromosome 5 and revealed additional-associated loci 47…”
Section: Scanning the Genomementioning
confidence: 93%
“…In a follow-up to this, microsatellite markers positioned this susceptibility allele on chromosome 5 at 5p15.2, with a protective allele at position 5q11.2 46. More recently, several studies have identified multiple gene loci associated with the risk of sarcoidosis, on chromosomes 1, 2, 5, 6, 9, 11, 12, and 20 33–36.…”
Section: Genetic Factorsmentioning
confidence: 99%
“…Replication of the susceptibility allele in BTNL2, rs2076530, was performed in an African-American family-based population, and in African-American and Caucasian case-control populations. In all 3 study populations there was a haplotype associated with sarcoidosis, but the association was much stronger in Caucasians (p = 0.0006) compared with the African-American family population (p = 0.03) or case-control population (p = 0.02) [69, 70, 73]. These authors suggested that while in Caucasians the effects of BTNL2 are independent of HLA class II genes, there may be an antagonistic interaction between these loci in African-Americans.…”
Section: Genetic Associations In Sarcoidosismentioning
confidence: 99%